The evolving role of pharmacovigilance and drug safety: The way forward for Bangladesh - Mainul, Haque; Asadul Mazid, Helali; Md. Jalaluddin, Iqbal (2014)
Adverse drug reactions are a major public health issue and safety of drugs is a major concern particularly among children, pregnant women, and the elderly. Every society has the right to be protected against such odds. There are multiple methods for detecting the adverse drug reactions at different stages of drug development and also in the market life of a new drug. Single system alone is not sufficient to cover all the demands. Therefore multiple methods are needed for observing and quantifying the adverse drug reactions. Monitoring of adverse drug reactions by applying well developed IT enabled system in primary and secondary health care also can be an effective measure. Adverse drug reactions should be taken into account more seriously and critically as often they are life threatening and a burden to the patient. Thus, more effort should be put in making methods available for detection of adverse drug reactions specially in post-marketing stage of a drug and only then it will be possible to ameliorate the risk-benefit ratio of a treatment. While major advancements of the discipline of pharmacovigilance have taken place in the West, not much has been achieved in Bangladesh. A number of clinical trials and studies are currently ongoing in Bangladesh which necessities an immense needs to understand and implement pharmacovigilance. In Bangladesh, the mindset of people working in regulatory agency and the Bangladesh Pharmaceutical companies needs to change regarding pharmacovigilance.